Development of an Original Integrated System for Heat Recovery from Coolant in the Machining Process and Investigation of Its Efficiency - Osman Şahin; Durmuş Karayel (Applied Sciences)
When a comparison is made between production methods, it will be seen that a significant amount of energy is consumed in machining processes and a large part of this energy is lost as waste heat. This is an important risk factor for both energy efficiency and environmental protection. During metalworking, a very high level of heat is generated at the cutting tool–workpiece interface. We have conducted a comprehensive literature study on this subject, but so far, no study has been found on the recovery of the heat generated in machining processes. Therefore, the aim and motivation of this study is to recover this waste heat to a certain extent. For this purpose, a comprehensive coolant temperature control and heat recovery system has been developed. This system, which was produced as a prototype, can be easily integrated into the machine tool and automatically adjust the coolant temperature to a certain constant temperature level and maintain this temperature value throughout the process. More importantly, it recovers the heat energy taken from the coolant and makes it useful. On the other hand, although it is not the subject of this study, cutting performance increases, coolant consumption decreases and tool life is extended with the cooling of the coolant. Thus, environmental risks are also reduced. Also, the efficiency and economic feasibility of the developed system were also examined. For this purpose, the energy amount consumed by the developed system and the machine tool were measured separately, and the total energy consumed was determined. Then, the consumed and recovered energy amounts were compared, and it was seen that the amount of energy recovered was more than the total amount of energy consumed. When the decrease in coolant and cutting-tool consumption is also taken into account compared to the classical cooling system, it is understood that the amortization period of the developed system is quite low. On the other hand, optimum conditions were investigated in order to provide maximum energy recovery. For this purpose, experiments were carried out by drilling 2592 holes on 27 samples, 96 holes in each sample, by taking the coolant solution ratio, cutting speed, and feed rate as variable parameters. The experimental results were evaluated using the Taguchi method. It has been observed that the system can be easily adapted to other machining processes, such as turning and milling, and that it has a high potential to increase energy efficiency and prevent environmental risks in this area.